Perlindungan Hak Asasi Manusia (HAM) Terhadap Wanita Yang Menjadi Korban Pemerkosaan Dan Tindak Pidana Pemerkosaan - Faturohman Faturohman; Hurotun Afifah; Mita Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
Rape is a sexual act committed against a person without consent or without explicit consent. This is a very serious form of sexual violence and violates human rights. Rape can occur in a variety of contexts, including during an intimate relationship, by someone you know, or even by a stranger. This can cause deep physical and emotional trauma to victims, as well as having far-reaching impacts on society as a whole. It is important to take steps to prevent rape and provide support to victims. Rape carried out on women or men usually causes very severe trauma to them. Usually, the person becomes uncomfortable, insecure, and afraid of meeting people. He will feel alone forever, and think about ending himself, because he thinks that he is no longer pure. Usually, rape is committed by someone or several individuals, known or unknown, who deliberately rape the victim. Rape may occur because the perpetrator likes the victim, or because the perpetrator wants revenge on the victim, or there is something else. Women are creatures of God Almighty who are very perfect, because they give birth and breastfeed. In Indonesia, there are still many cases of rape that occur against women and children. The motive may be because the perpetrator likes the victim, or the perpetrator just wants revenge on the victim, or it was planned long ago by the perpetrator. Rape against women or girls is a form of sexual violence that occurs when someone commits a sexual act against a woman without her consent. This may include vaginal, anal, or oral penetration, as well as other sexual acts carried out with violence, threats, coercion, or the woman's inability to provide valid consent. Rape against women is often a form of expression of systematic gender inequality and domination. It is important to remember that rape does not only happen to women, but can also happen to men or individuals of various other gender identities. Nevertheless, rape of women is often in the spotlight due to its high prevalence and serious impact on the well-being of women and society as a whole. Therefore, it is important to continue fighting sexual violence and fighting for gender equality to create a safe and inclusive society for all individuals.